An autopsy study of road traffic accident cases at tertiary care center, Mandya, Karnataka - B. M., Rakshitha; Y., Chinmayi; Kumar, Vijay; U., Kumar (International Journal of Research in Medical Sciences, 2023)
Background: Road traffic accidents represent a pervasive global crisis resulting in the loss of millions of lives and countless injuries annually. According to the world health organization (WHO), over 1.3 million people die in road traffic accident every year, and an additional 20-50 million are injured or disabled. Objective was to study the demographic patterns in these cases of RTA in and around AIMS B. G. Nagar, India. Methods: It was a cross sectional study of all medico legal necropsies of road traffic accidents, Data was collected between January 2022 to June 2023 at the mortuary of the department of forensic medicine and toxicology, AIMS, B. G. Nagar, and Karnataka, India. Collected data was analysed. Results: During the study period 117 (40.20%) were road traffic accidents, according to this study road traffic accidents were more 30 (25.64%) in old age groups and males 105 (89.74%) were majorly affected. Majority of the accidents 41 (35%) predominantly occurred during evening to midnight hours on highways 65 (55.55%), light vehicles (37.61%) were most frequently engaged in road traffic accident and the most common site of injury was head 98 (83.76%), and cause of death was due to intracranial hemorrhages (49.57%) and among the pattern of intracranial hemorrhage we observed high number of (32.47%) combination of subdural hemorrhages and sub-arachnoid hemorrhages. Conclusions: Through this study we want to create awareness and deploy safety measures to prevent RTA.